Can well-being between Sub-Saharan Africa (SSA) and Organization for Economic Cooperation and Development (OECD) member countries converge? - Adamu, Peter; Kaliappan, Shivee Ranjanee; Omer, Abdalla Sirag Fagir; Chenbap, Ruth John (Springer, 2015)
This study investigates the convergence of well-being between Sub Saharan Africa (SSA) and Organization for Economic Cooperation and Development (OECD) member countries during the period 1980–2014. The gap in living standard was examined from a steady state represented by the average income of OECD countries. Applying the unit root estimation technique to test for convergence with and without structural breaks, the result shows that; among a total of 43 countries studied, about 14 % are converging towards the average of OECD average. When the shock caused by the economic crisis of 2008 was factored into the analysis, the gains of about five countries out of the six converging disappeared. These results are disturbing owing to the fact that countries in the Asian region that started almost at the same level with SSA have converged to form a convergence club. Therefore, a lot more effort is needed from the government and stake holders in most countries in SSA to improve on the determinants of growth like good health care, quality institutions, better education and commitments to pursue developmental programmes which will boost the income of an average African to acquire better life.